Answer:
Step-by-step explanation:
bvfghhgf
<span>First rewrite y - 2x<span> 2</span> = 8 x + 5 as</span>
y = 2x<span> 2</span><span> + 8 x + 5 </span>
Complete square and determine vertex.
y = 2(x<span> 2</span><span> + 4x + 4) - 8 + 5 </span>
= 2(x + 2)<span> 2</span><span> - 3 </span>
<span>vertex at (- 2 , - 3) </span>
If parabola is translated 3 units to the left and 2 units up its vertex is also translated 3 units to the right and 2 units up .
<span>vertex after translations is at: (-2 - 3 , - 3 + 2) = (-5 , -1)</span>
Answer:
c
Step-by-step explanation:
because if you look at the line below it it shows 180 degrees because it is a straight line if that makes sense. if not just trust me.
Answer:
<h3>
f(x) = 5x² + 2x</h3><h3>
g(x) = 6x - 6</h3>
Step-by-step explanation:
![\dfrac{5x^3-8x^2-4x}{6x^2-18x+12}\\\\6(x^2-3x+2)\ne0\ \iff\ x=\frac{3\pm\sqrt{9-8}}{2}\ne0\ \iff\ x\ne2\ \wedge\ x\ne1\\\\\\\dfrac{5x^3-8x^2-4x}{6x^2-18x+12}=\dfrac{x(5x^2-8x-4)}{6(x^2-3x+2)}=\dfrac{x(5x^2-10x+2x-4)}{6(x^2-2x-x+2)}=\\\\\\=\dfrac{x[5x(x-2)+2(x-2)]}{6[x(x-2)-(x-2)]} =\dfrac{x(x-2)(5x+2)}{6(x-2)(x-1)}=\dfrac{x(5x+2)}{6(x-1)}=\dfrac{5x^2+2x}{6x-6}\\\\\\f(x)=5x^2+2x\\\\g(x)=6x-6](https://tex.z-dn.net/?f=%5Cdfrac%7B5x%5E3-8x%5E2-4x%7D%7B6x%5E2-18x%2B12%7D%5C%5C%5C%5C6%28x%5E2-3x%2B2%29%5Cne0%5C%20%5Ciff%5C%20x%3D%5Cfrac%7B3%5Cpm%5Csqrt%7B9-8%7D%7D%7B2%7D%5Cne0%5C%20%5Ciff%5C%20x%5Cne2%5C%20%5Cwedge%5C%20x%5Cne1%5C%5C%5C%5C%5C%5C%5Cdfrac%7B5x%5E3-8x%5E2-4x%7D%7B6x%5E2-18x%2B12%7D%3D%5Cdfrac%7Bx%285x%5E2-8x-4%29%7D%7B6%28x%5E2-3x%2B2%29%7D%3D%5Cdfrac%7Bx%285x%5E2-10x%2B2x-4%29%7D%7B6%28x%5E2-2x-x%2B2%29%7D%3D%5C%5C%5C%5C%5C%5C%3D%5Cdfrac%7Bx%5B5x%28x-2%29%2B2%28x-2%29%5D%7D%7B6%5Bx%28x-2%29-%28x-2%29%5D%7D%20%3D%5Cdfrac%7Bx%28x-2%29%285x%2B2%29%7D%7B6%28x-2%29%28x-1%29%7D%3D%5Cdfrac%7Bx%285x%2B2%29%7D%7B6%28x-1%29%7D%3D%5Cdfrac%7B5x%5E2%2B2x%7D%7B6x-6%7D%5C%5C%5C%5C%5C%5Cf%28x%29%3D5x%5E2%2B2x%5C%5C%5C%5Cg%28x%29%3D6x-6)